Investigating Potential Biomarkers in Autism Spectrum Disorder - Bridgemohan, Carolyn; Cochran, David M.; Howe, Yamini J.; Pawlowski, Katherine; Zimmerman, Andrew W.; Anderson, George M.; Choueiri, Roula; Sices, Laura; Miller, Karen J.; Ultmann, Monica; Helt, Jessica; Forbes, Peter W.; et al. (Frontiers in Integrative Neuroscience, 2019)
Background: Early identification and treatment of individuals with Autism Spectrum Disorder (ASD) improves outcomes, but specific evidence needed to individualize treatment recommendations is lacking. Biomarkers that could be routinely measured within the clinical setting could potentially transform clinical care for patients with ASD. This demonstration project employed collection of biomarker data during regular autism specialty clinical visits and explored the relationship of biomarkers with clinical ASD symptoms. Methods: Eighty-three children with ASD, aged 5-10 years, completed a multi-site feasibility study integrating the collection of biochemical (blood serotonin, urine melatonin sulfate excretion) and clinical (head circumference, dysmorphology exam, digit ratio, cognitive and behavioral function) biomarkers during routine ASD clinic visits. Parents completed a demographic survey and the Aberrant Behavior Checklist-Community. Cognitive function was determined by record review. Data analysis utilized Wilcoxon two-sample tests and Spearman correlations. Results: Participants were 82% male, 63% White, 19% Hispanic, with a broad range of functioning. Group means indicated hyperserotonemia. In a single regression analysis adjusting for race and median household income, higher income was associated with higher levels of blood serotonin and urine melatonin sulfate excretion levels (p=.004 and p=.04, respectively). Melatonin correlated negatively with age (p= 0.048) and reported neurologic problems (p=0.02). Dysmorphic status correlated with higher reported stereotyped behavior (p=0.02) and inappropriate speech (p=0.04). Conclusions: This demonstration project employed collection of multiple biomarkers, allowed for examination of associations between biochemical and clinical measures, and identified several findings that suggest direction for future studies. This clinical research model has promise for integrative biomarker research in individuals with complex, heterogeneous neurodevelopmental disorders such as ASD.